Scripture as interface: a hermeneutical reflection on a concept based in media theory - Oorschot, Frederike van (Cursor_, 2022)
Following Michael Hemenway’s description of the Bible as interface, Frederike van Oorschot reflects the dogmatic implications of this description. Understanding scripture as interface describes scripture as a zone of encounter, prompting questions about its affordances and highlights the relational, anarchic, and collaborational character of scripture.